Steganography System Using More Lsbs (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Steganography is the method of hiding message in a cover object for cover communication. The article deals with the steganography system which hides text inside images without losing of data (BMP, PNG, TIFF and GIF). The secret message is hidden in the cover image using Last Significant Bit (LSB) method. Paper presents functionalities of the developing software, using LBS methods. Visual and statistical analysis of LBS method indicate the good results of its application.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.